Pengembangan Puzzle Berbasis AR (Augmented Reality) Untuk Menumbuhkan Nilai Bermasyarakat Anak Usia Dini - Amanatul Uluwiyah; Alif Mudiono; Eny Nur Aisyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: (1) develop an Augmented Reality-based Educational Game Tool puzzle as a medium for instilling social values in early childhood, and (2) assess the feasibility of the tool through validation by content experts and media experts. This research is a development study of the Educational Game Tool using Thiagarajan's 4-D model. The subjects of this study were 10 students from group B at TK Nurul Islam Jatirejo. Data analysis employed a quantitative descriptive method to determine the media’s feasibility. The development of the APE Puzzle Puzila has passed four stages of the 4-D model, namely Define, Design, Develop, and Disseminate. The results indicate that the Puzzle media is feasible for use by group B at TK Nurul Islam Jatirejo for teaching social values, as evidenced by average validation scores from content experts (4.1), media experts (4.3), teachers (4.2), and an average student trial response score of 1, all falling into the feasible category.